PERLINDUNGAN KONSUMEN DITINJAU DARI PENGOBATAN TRADISIONAL RAMUAN DAN KETERAMPILAN DI KECAMATAN SENAPELAN KOTA PEKANBARU - Harani Fitryan; Mardalena Hanifah; Riska Fitriani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
This study was motivated by the traditional medicine which is used as an option by some Indonesian society as complementary to conventional treatment so as to encourage the establishment of many traditional medical practices that do not have permission, especially in Sub Senapelan Pekanbaru. Based on this, then it is fitting needs to be done to consumer protection in this case is a patient of traditional medicine. The government is required to provide guidance, supervision and guidance so that this can be accounted for traditional medicine and security benefits in accordance with the purpose of the Act No. 8 of 1999 on Consumer Protection and Law No.36 of 2009 on Health.The author raised this issue in order to determine how the shape of consumer protection in Pekanbaru City Senapelan District and the implementation of the fulfillment of the rights of consumers in this study were patients of traditional medicine as set out in the Consumer Protection Act.This study is a descriptive sociological research, because in this study the authors directly conduct research on the location or place under study in order to provide a complete and clear picture of the problem under study.This research was carried out on the practice of traditional medicine in the District Senapelan Pekanbaru, while the population and the sample is a whole party relating to the issues examined in this study. Source of data used in the form of primary data, secondary and tertiary, while the data collection techniques in this study of interviews, questionnaires and literature study. Based on the results, it can be concluded that the Consumer Protection Act expressly already regulate the rights and obligations of consumers, businesses responsibilities and things should not be done by businesses. But in practice it is still a violation of rules that could harm consumers.Based on data obtained from the field, there are still many traditional medical practices that do not have the permission which in this case has violated the rules of health ministers No. 1076 / Menkes / SK / VII / 2003, Article 4, Paragraph 1, which requires that every practice of traditional medicine has a registered license and a license to practice. Consumer rights are also many who still have not been met, such as providing the unfulfilled promise in violation of the Consumer Protection Act Article 8, paragraph 1 (f), and does not provide clear information to patients from both treatment techniques to the provision of drugs in violation Health Law Article 56.Keywords: Consumer Protection, Patient, Traditional Medicine